Mauritian Bhojpuri Folk Songs: Psychological Worship and Cultural Tradition - Jayganesh Dawosing (Recent Research Advances in Arts and Social Studies Vol. 3, 2023)
This chapter discusses about the psychology of worship in the Mauritian Bhojpuri folk songs. Songs from the Mauritian "Geet-Gawai" (Bhojpuri songs sung before the wedding ceremony in Mauritius). Contemporary musical discourse is of utmost interest. Bhojpuri music is getting more and more vibrant today. Themes like pantheism, fear and awe in religion, nature worship or nature mysticism will be discussed. How do these singers perceive worship? Which theories are reflected in these songs? For how long will this tradition of worship exist? For the study, three songs have been chosen from the Mauritian Geet Gawai which are prevalent during the performance. Mauritius Folk melodies from Bhojpur express the idea that reality and divinity are one and the same. All things belong to an everlasting, merciful God. In the examination, Baruch Spinoza’s theory of Pantheism comes out on top, and similarities with Advaita’s Vedas-philosophy (non-dualism) are also evident. This ceremony depicts that there are no barriers of caste and class, as it contributes in the making of a strong multiracial community identity. It is no longer only for women, as men are also actively participating in it. Geet Gawai is an ever-evolving folkloric ritual. Some organizations use modern instruments, which is something that should be supported. In addition to the Mauritian Sega, the Ministry of Arts and Culture and the Ministry of Tourism should host the Geet Gawai in the neighborhood hotels to provide visitors with a more comprehensive introduction to Mauritian culture.